Effectiveness of Padlet-Based Interactive Media to Increase Literacy in Environmental Change Material for Vocational School Students - Nurafiani, Gita; Alimah, Siti; Irsadi, Andin; Marianti, Aditya (Universitas Negeri Semarang, 2025)
Padlet-based interactive media can be used as a learning resource for students to increase environmental literacy. Based on the results of initial observations, it has not been optimal in linking environmental change material with environmental literacy. Students do not understand environmental literacy in a broad and global perspective. So students’ environmental literacy skills are lacking. The aim of this research is to determine the effectiveness of Padlet-based interactive media in increasing environmental literacy in vocational school students’ environmental change material. his study uses a quantitative method. The test subjects in this research were class X students at Al Ittihad Bringin Vocational School for the 2024/2025 academic year. The instruments used are multiple choice tests and LKPD. The results of this research are in the form of Padlet-based interactive me dia to increase environmental literacy that is valid, easy to understand and practical. The results of the effectiveness of Padlet-based interactive media in increasing environmental literacy can be seen from the N-gain value in the knowledge aspect of 0.88 in the high category, the attitude aspect of 0.82 in the high category, and the knowledge skills aspect of 0.81 in the high category. High criteria indicate that Padlet-based interactive media is effective in increasing students’ environmental literacy, especially in environmental change material.